2016
DOI: 10.1016/j.foodpol.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Consumer preferences regarding country of origin for multiple meat products

Abstract: Despite the growing use of country of origin (CoO) information and labels on food, the extent to which consumers really value this information is unclear. In an effort to understand this issue we present results of a hypothetical discrete choice experiment examining consumer willingness-topay for CoO information about meat and meat products. Our results reveal that CoO information is positively valued for all the food products we consider. However, it is relatively less important compared to other food attribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
53
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 34 publications
5
53
1
Order By: Relevance
“…For example, Balcombe et al . () examined various fresh and processed meat products and found that although COO was positively valued for all products it was not the most highly valued product attribute for the majority. Interestingly, it was the most important attribute for most fresh meat products, but not for processed products.…”
Section: Consumer Use Of Coolmentioning
confidence: 99%
“…For example, Balcombe et al . () examined various fresh and processed meat products and found that although COO was positively valued for all products it was not the most highly valued product attribute for the majority. Interestingly, it was the most important attribute for most fresh meat products, but not for processed products.…”
Section: Consumer Use Of Coolmentioning
confidence: 99%
“…In a recent review of this literature, Balcombe et al . () note that consumers, across countries, appear to place a positive value on CoOL for meat, though there is limited research conducted in the UK. One exception is Meas et al .…”
Section: Hedonic Analysis Cool and The Horsemeat Incidentmentioning
confidence: 99%
“…This research has been conducted in many countries and much of the literature has focussed on beef. In a recent review of this literature, Balcombe et al (2016) note that consumers, across countries, appear to place a positive value on CoOL for meat, though there is limited research conducted in the UK. One exception is Meas et al (2014) who used a discrete choice experiment (DCE) to assess British consumers' preferences for domestic and imported beef.…”
Section: Hedonic Analysis Cool and The Horsemeat Incidentmentioning
confidence: 99%
See 1 more Smart Citation
“…Country of origin labels are generally poor quality indicators. Not surprisingly, Balcombe et al () show that other attributes are more highly valued by consumers than country of origin information.…”
mentioning
confidence: 99%